Tezės 1. World Colorectal CONFERENCE - chirurgija, Lietuvos (Lietuvos chirurgija, 2013)
International Society of University Colon and Rectal Surgeons (ISUCRS)Interim meeting in Vilnius 2013World Colorectal C O N F E R E N C EMay 31 – June 1, 2013Vilnius, Lithuania